Kriteria Desain Hunian bagi Penyandang Disabilitas Penglihatan: Pendekatan Berbasis Pengalaman Pengguna dan Strategi Non-Visual - Rizka Nurhalisya; Muhammad Fauzan Amir; Nida Mujahidah Zharfani; Eggi Septianto (JURNAL RUANG / ISSN : 2085-6962, 2026)
People with visual impairments often develop a high level of independence in their living environment due to repeated daily interactions. However, this independence is often achieved through personal adaptation rather than intentional architectural design support. This study aims to identify residential design criteria that improve orientation and navigation for the visually impaired through non-visual strategies. A descriptive qualitative method was used, combining a review of national and international literature (2020-2024) and in-depth interviews with three visually impaired respondents. The results of the study formulated specific design criteria that include tactile elements, consistent spatial organization, the use of materials with different textures, and optimal lighting for users with low vision. These findings provide guidance for architects to create more inclusive and accessible housing.